A Shape‐Programmable Hierarchical Fibrous Membrane Composite System to Promote Wound Healing in Diabetic Patients. Issue 11 (17th January 2022) - Li, Weichang; Jiang, Laibo; Wu, Shujie; Yang, Shiwen; Ren, Lin; Cheng, Bin; Xia, Juan
Abstract: Chronic wound infection is one of the critical complications of diabetes and is difficult to cure. Although great efforts have been made, the development of special dressings that serve as therapeutic strategies to effectively promote wound healing in diabetic individuals remains a major challenge. In this study, a shape‐programmable hierarchical fibrous membrane composite system is developed for synergistic modulation of the inflammatory microenvironment to treat chronically infected wounds. The system comprises a functional layer and a shape‐programmable backing layer. A temperature‐responsive shape‐memory mechanism achieves biaxial mechanically active contractions of diabetic wounds in a programmable manner. To summarize, the membrane system combines antimicrobial activity, controlled drug release according to the need of wound healing, mechanical modulation with shape‐programmable, robust adhesion, and on‐demand debonding to biological tissue to rationally guide chronic wound management. A synergistic combination of antibacterial fiber network and released drugs shows broad‐spectrum antibacterial activity. In vitro and in vivo evaluations indicate the dressing efficiency in promoting and supporting wound healing. The insights from this study demonstrate the effectiveness of a hierarchical composite membrane system with shape‐programmability as a potential treatment in the care of diabetic wounds. Abstract : Chronic wound healing is impaired in people suffering from diabetes mellitus. Here, a hierarchically structured, shape‐programmable dressing is developed, which elicits accelerated wound healing of chronic diabetic wound tissue. Given the scope for improving the lives of people suffering from diabetes, it is believed that this work could better instruct wound care and guide clinical intervention in hospitals.